Hubungan Kegiatan Ekstrakulikuler Kepramukaan Terhadap Kedisiplin Siswa di SD Negeri Inpres 1 Apo: Penelitian - Junet Johana Tary; Nurul Mutmainnah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to identify the relationship between Scouting extracurricular activities and the discipline character of students at SD Negeri Inpres 1 APO. The research sample comprises elementary school students from the aforementioned school. Descriptive statistics reveal that the mean score for Scouting extracurricular activities is 47.74 with a standard deviation of 8.089, whereas the mean score for student discipline character is 47.77 with a standard deviation of 8.014. ANOVA analysis indicates that the regression model is statistically significant (F(1, 48) = 236.823, p < 0.001), with a regression coefficient of 0.497 (p < 0.001). These findings demonstrate a strong positive relationship between Scouting extracurricular activities and student discipline character. Although the data do not follow a normal distribution, hypothesis testing indicates that Scouting extracurricular activities significantly influence student discipline character. Therefore, it is recommended that the school enhance support and facilities for Scouting extracurricular activities to foster better discipline character in students.